SINGLE-DOSE PRULIFLOXACIN VERSUS SINGLE-DOSE PEFLOXACIN IN THE TREATMENT OF ACUTE UNCOMPLICATED URINARY TRACT INFECTION IN WOMEN - M. CERVIGNI; G. ORTICELLI; M. BOLOGNA; F. NATALE; E. SALVATORI; G. DI LORETO; P. DIONISIO (Urogynaecologia International Journal, 2010)
The aim of the study was to compare the efficacy and safety of singledose prulifloxacin vs. single-dose pefloxacin in the treatment of patients with acute uncomplicated urinary tract infections. Two hundred and thirty-one female out-patients were considered microbiologically evaluable and randomly treated with 600 mg prulifloxacin (116 patients) or 800 mg pefloxacin (115 patients). The most commonly isolated uropathogen at baseline was Escherichia coli (71.4%), followed by Proteus mirabilis (10.8%) and Klebsiella pneumoniae (7.8%). Five-seven days posttreatment, the eradication rate was 97.4% and 92.2% in the prulifloxacin and pefloxacin group, respectively. The one-tailed 95% confidence interval analysis showed the equivalence of treatments. Four weeks from treatment no relapses, reinfections or superinfections were observed. The clinical success rates were 92.2% in the prulifloxacin and 84.3% pefloxacin groups. The safety profile was very good with both drugs. The results of the study make it possible to consider prulifloxacin a possible therapeutic option in patients with acute uncomplicated UTIs.